Performa dan Profil Organ Ayam Pedaging dengan Pemberian Jamu Kombinasi Jahe, Temulawak, Lempuyang dan Madu - Mustika, Aulia Andi; Andriyanto, Andriyanto; Muhamad, Kusdiantoro; Sutardi, Lina Noviyanti; Khonsa, Khonsa; Ananta, Alifin Wisnu; Leluala, SM (Jurnal Veteriner; Vol 23 No 4 (2022)DO - 10.19087/jveteriner.2022.23.4.548, 2022)
The use antibiotic growth promoters (AGP) can cause antibiotic residues and microorganism resistance, so it is prohibitied by the government.  Jamu is an Indonesian herbal ingredient that can be used as an alternative in overcoming this problem.  The aim of the study was to determine the effective concentration of a combination of ginger, curcuma, wild ginger, and honey herbs in improving the performance and profile of broiler chickens without changing the organoleptic properties of the meat.  The study used 36 Cobb strain day old chicks (DOC) which were reared up to 32 days of age.  The study used a completely randomized design with the addition of combination herbal medicine in drinking water as much as 0% (control), 1.25% (P1), 2.5% (P2), and 5% (P3).  The variabels observed included performance (feed and drink consumption, body weight gain, final weight, feed conservation ratio (FCR), performance index (IP), mortality), organ profiles (weight of liver, hearts, lungs and spleen), and weight and length of the duodenum, jejeum, ileum of broiler chickens followed by organoleptic test on broiler chicken meat.  The result showed that P1, P2, and P3 significanly (p<0.05) could increase the final weight and body weight gain. Carcass weight, abdominal fat weight, FCR, IP, mortality, and organ profile showed no significant difference (p>0.05) between treatment and control.  Research shows that the combination of ginger, temulawak, lempuyang, and honey with concentration of 5% can improve performance without changing the organ profile of broiler chickens and organoleptic broiler chicken meat.